The Role of Social Media for the Elderly in Lembean Village, Kauditan District, North Minahasa Regency - Tangkudung, Joanne P. M.; Tulung, Lingkan E. (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
This study aims to determine the role of social media for the elderly in Lembean Village, Kauditan District. Based on the definition of WHO (World Health Organization), the elderly are people who are in the age range of over 60 years. The use of social media can provide the elderly with social activities and communication to live a happy and joyful old age, the theory of social activity Successful aging depends on how an elderly person feels satisfaction in doing activities and maintaining those activities. Spradley's qualitative research method; study of individuals/groups with the aim of describing cultural characteristics more deeply systematically in their own space and time. the number of informants is 4 people, namely 2 elderly women and 2 elderly men using purposive sampling techniques, in-depth interview data collection techniques, analyzed and described. The results of the study obtained the role of social media for the elderly in Lembean Village, namely; a means of social activity through whats app groups with family, elderly community groups, religious groups; a means of entertainment activities by exposing daily activities both at home and outside the home; a means of information sources of joy or sorrow and events in the outside world through Facebook, a means of economic activity exposing sales for elderly people who are still productive. Social media becomes a means of digital activity for the elderly to fill their time at home, a source of information and a means of immortalizing activities with photos.